Effect of seed pelleting on yield and storage quality in Fennel (Foeniculum vulgare Mill): Seed pelleting in fennel - Nikumbhe, Prashant H; Shivanna, Shantharaja C (Journal of Spices and Aromatic Crops, 2023)
The current investigation on the effect of seed pelleting on germination, plant establishment and seed yield in fennel was carried out in two seasons during Rabi 2017 and 2018. The experiment consisted of 17 seed pelleting treatments along with the control. Field emergence (93.1 %), umbels per plant (26.61) and seed yield (1376 kg ha-1) were highest in seeds pelleted with Lignite +Azospirillum and higher number of seeds per plant (397) was obtained in Lignite+Gum Arabic, whereas, days to 50 % field emergence, plant height and test weight showed non-significant differences among the treatments. Lignite + gum Arabic pelleting recorded maximum seed germination (65 %) at the end of six months storage period. In general, seeds pelleted with Lignite and coated with Azospirillum showed better performance both in terms of yield and storability.